Development of a Psychological Intervention to Address Anxiety During Pregnancy in a Low-Income Country - Atif, Najia; Nazir, Huma; Zafar, Shamsa; Chaudhri, Rizwana; Atiq, Maria; Mullany, Luke C.; Rowther, Armaan A.; Malik, Abid; Surkan, Pamela J.; Rahman, Atif (Frontiers in Psychiatry, 2020)
Background: One in five women suffer from anxiety during pregnancy. Untreated anxiety is a risk factor for postnatal depression and is associated with adverse birth outcomes. Despite the high prevalence of prenatal anxiety in low- and middle-income countries (LMICs), efforts to develop and evaluate context-specific approaches in these settings are lacking. We aimed to develop a culturally appropriate, feasible, and acceptable psychological intervention for perinatal anxiety in the context of a low-income population in Pakistan. Methods: We conducted this research in Rawalpindi District at the Obstetrics Department of the Holy Family hospital, a government facility catering to a mixture of low-income urban, peri-urban, and rural populations. We used a mixture of research methods to: a) investigate the clinical, cultural, and health-service delivery context of perinatal anxiety; b) select an evidence-based approach that suited the population and health-delivery system; c) develop an intervention with extensive reference documentation/manuals, and; d) examine issues involved in its implementation. Qualitative data were collected through in-depth interviews and Focus Group Discussions, and analyzed using Framework Analysis. Results: Informed by the qualitative findings and review of existing evidence-based practices, we developed the “Happy Mother, Healthy Baby” intervention, which was based on principles of cognitive behavior therapy. Its evidence-based elements included: developing an empathetic relationship, challenging thoughts, behaviour activation, problem-solving, and involving family. These elements were applied using a 3-step approach: 1) learning to identify unhealthy or unhelpful thinking and behavior; 2) learning to replace unhealthy or unhelpful thinking and behavior with helpful thinking and behavior, and; 3) practicing thinking and acting healthy. Delivered by non-specialist providers, the intervention used culturally appropriate illustrations and examples of healthy activities to set tasks in collaboration with the women to encourage engagement in helpful behaviors. Feedback from the non-specialist providers indicated that the intervention was acceptable, feasible, and perceived to be helpful by the women receiving it. Conclusion: This new psychosocial intervention for perinatal anxiety, based on principles of cognitive behavior therapy and delivered by non-specialists, has the potential to address this important but neglected condition in LMIC.